2017
DOI: 10.1098/rsta.2015.0385
|View full text |Cite
|
Sign up to set email alerts
|

On the attempts to measure water (and other volatiles) directly at the surface of a comet

Abstract: The Ptolemy instrument on the Philae lander (of the Rosetta space mission) was able to make measurements of the major volatiles, water, carbon monoxide and carbon dioxide, directly at the surface of comet 67P/Churyumov–Gerasimenko. We give some background to the mission and highlight those instruments that have already given insights into the notion of water in comets, and which will continue to do so as more results are either acquired or more fully interpreted. On the basis of our results, we show how comets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The Rosetta mission approached the nucleus of the comet 67P/Churyumov-Gerasimenko and delivered the Philae lander to the surface in 2014 [11]. This mission showed that comets are highly heterogeneous in their composition, resulting from their diurnal cycles [12]. Although having planets pelted with cometary snowballs is an appealing model to deliver volatiles, the C, N and O isotopic evidence rule out most comets as the source of most inner Solar System water.…”
mentioning
confidence: 99%
“…The Rosetta mission approached the nucleus of the comet 67P/Churyumov-Gerasimenko and delivered the Philae lander to the surface in 2014 [11]. This mission showed that comets are highly heterogeneous in their composition, resulting from their diurnal cycles [12]. Although having planets pelted with cometary snowballs is an appealing model to deliver volatiles, the C, N and O isotopic evidence rule out most comets as the source of most inner Solar System water.…”
mentioning
confidence: 99%